Effect of brushing on surface roughness, fluoride release, and biofilm formation with different tooth-colored materials - Anisha Komalsingsakul; Ratchapin Laovanitch Srisatjaluk; Pisol Senawongse (Elsevier, 2022)
Background/purpose: Tooth brushing, material mechanical ageing procedure, is the most effective way in removing biofilm. The purpose of this study was to investigate the surface roughness, fluoride-release, and S. mutans biofilm formation on various tooth-colored restorative materials before and after brushing. Materials and methods: Discs of materials, a nanocomposite (Filtek Z350XT; CO), a giomer (Beautifil II; GIOMER), a resin-modified glass-ionomer material (Fuji II LC; RMGI), and a conventional glass-ionomer material (Fuji IX GP Extra; GI), were prepared, polished with abrasive discs (SofLex), and divided into brushed and not brushed groups. The surface roughness of specimens was observed using a contact profilometer, fluoride-release was measured using a fluoride-specific ion electrode, and S. mutans biofilm formation, biovolume and live/dead cells, was observed under a confocal laser scanning microscope. Results: Higher roughness was observed on GI and RMGI than on CO and GIOMER. Brushing had no effect on the roughness. The fluoride-release of GI and RMGI was higher than that of GIOMER. The fluoride-release decreased after brushing in all materials. The biovolume of S. mutans was not significantly different between GIOMER, RMGI and GI, while CO showed the highest. Brushing resulted in a higher biovolume for all materials, except CO, which showed no change. After brushing, all the tested materials demonstrated identical biovolumes. There were no significant differences in live/dead cells among all groups. Conclusion: Brushing demonstrated a negative effect on the fluoride-release and biovolume of S. mutans biofilms for all tested materials except nanocomposites.